2011
DOI: 10.1007/s00417-011-1797-3
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of the ciliary epithelium with retinal neuronal and photoreceptor cell differentiation in human eyes with retinal detachment and proliferative vitreoretinopathy

Abstract: Our observations suggest that EGFR-positive CE cells in the adult human eye in vivo with RD and PVR form "neurosphere-like" structures; their differentiation seems to be directed towards the neural and photoreceptor lineage, and not towards glial formation. In the adult human eye, the CE in a pathological retinal environment such as RD might provide a spontaneous source of donor cells for retinal transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 50 publications
(58 reference statements)
1
9
2
Order By: Relevance
“…In this study, hyperplasia of the CB, forming "neurosphere-like" structures were found. There were no GFAP+ cells, but unlike in our study, a few rhodopsin+ cells were found in the vicinity of the CE (106). Further analysis of more eyes with retinal damage may be needed to clarify the exact expression patterns.…”
Section: Does the Adult Human Cb Harbor Stem Cells?contrasting
confidence: 83%
“…In this study, hyperplasia of the CB, forming "neurosphere-like" structures were found. There were no GFAP+ cells, but unlike in our study, a few rhodopsin+ cells were found in the vicinity of the CE (106). Further analysis of more eyes with retinal damage may be needed to clarify the exact expression patterns.…”
Section: Does the Adult Human Cb Harbor Stem Cells?contrasting
confidence: 83%
“…Therefore, EGF is considered a major factor in the development of PVR [8,11]. In this study, we found that EGF-dependent proliferation and migration in RPE cell were inhibited by 1.0 μM AF (Fig 5).…”
Section: Discussionsupporting
confidence: 51%
“…Several groups have already indicated that EGF enhances RPE cell survival and can stimulate proliferation and migration of RPE cells through activation of the EGFR signaling pathway [68]. Some studies show that the activation of EGF seems to be an important factor of the pathogenesis of PVR [911]. …”
Section: Introductionmentioning
confidence: 99%
“…The vitreous was extracted with a 5-mL syringe, following the aforementioned steps at different time points (3,7,14,21, and 28 days). The test was processed according to instructions provided in the ELISA kit (LifeSpan Biosciences, Seattle, WA).…”
Section: Detection Of Egf Content In the Vitreousmentioning
confidence: 99%